DOI: 10.11606/d.11.2020.tde-07052020-102744
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos produtivos, qualitativos e fisiológicos do pimentão submetido à aplicação foliar de extrato de >i<Ascophyllum nodosum>/i< e suplementação luminosa

Abstract: Dissertação apresentada para a obtenção do título de Mestre em Ciências. Área de concentração: Fitotecnia Piracicaba 2020 Alessandro Sabino da Silva Engenheiro Agrônomo Aspectos produtivos, qualitativos e fisiológicos do pimentão submetido à aplicação foliar de extrato de Ascophyllum nodosum e suplementação luminosa versão revisada de acordo com a resolução CoPGr 6018 de 2011

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(47 reference statements)
1
0
0
Order By: Relevance
“…Nantes, differences were observed between temperatures, but not among the doses of biostimulant (Table 4). Similar to these results, Silva et al (2018) demonstrated that the Ascophyllum nodosum extract has inhibitory effects on the growth of Celosia cristata.…”
Section: Germination and Seedling Growth At Different Temperaturessupporting
confidence: 84%
“…Nantes, differences were observed between temperatures, but not among the doses of biostimulant (Table 4). Similar to these results, Silva et al (2018) demonstrated that the Ascophyllum nodosum extract has inhibitory effects on the growth of Celosia cristata.…”
Section: Germination and Seedling Growth At Different Temperaturessupporting
confidence: 84%